2006
DOI: 10.1111/j.0105-1873.2006.0847c.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatitis to α‐lipoic acid in an anti‐wrinkle cream

Abstract: In the mid nineties, the major producers and importers withdrew 'acid' CONTACT POINTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Thus, application every other day for the first few weeks may help improve tolerance. Contact dermatitis has also been reported (39). N.V. Perricone M.D.…”
Section: Clinical Use Of Alpha Lipoic Acidmentioning
confidence: 87%
“…Thus, application every other day for the first few weeks may help improve tolerance. Contact dermatitis has also been reported (39). N.V. Perricone M.D.…”
Section: Clinical Use Of Alpha Lipoic Acidmentioning
confidence: 87%
“…The reduction of TETD in blood plasma has been previously reported (22). The role of mixed disulfide formation in protein haptenation leading to skin sensitization has only been investigated in a few cases with MBT (18), lipoic acid (23), and diallyl disulfide from garlic (24). BSA, which is 80% homologous to human serum albumin (HSA), was used as an analytical tool to examine protein–TETD disulfide formation.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pig studies with MBT and several structural analogues demonstrated that sensitization was most likely a result of protein haptenation via disulfide formation [34]. ACD cases which have also been reported for chemicals like diallyl disulfide [35] and lipoic acid [36] which are thiols further indicate that disulfide formation may be a common mechanism for chemical thiol haptenation. The conclusion that MBT/MBTS haptenates proteins via disulfide formation was supported by enzyme inhibition and protein-binding studies where binding of MBTS to enzymes (reductases) and other protein cysteine residues was through disulfide formation [37].…”
Section: Nonelectrophilic Haptensmentioning
confidence: 99%